The complexities of research ethics when therapists become research subjects: power, privacy, and professional boundaries in psychotherapy research - Yonatan-Leus, Refael; Shefler, Gaby (Psychotherapy research, 2025)
The focus on therapist variables and characteristics has significantly increased in psychotherapy research in recent years. While ethical considerations for patient-participants are well-established, the unique ethical dimensions of therapist-subjects remain underexplored. This theoretical paper examines three critical ethical aspects specific to therapist-participants: power dynamics in hierarchical relationships, personal-professional boundary issues, and confidentiality challenges. We analyze how these considerations manifest particularly in training contexts where researchers often hold supervisory roles over therapist-subjects (e.g., faculty supervising student-therapists). The paper explores the complex interplay between informed consent and institutional hierarchies, especially when participation may be perceived as professionally expected rather than voluntary. We examine the implications of recording and analyzing therapy sessions that expose therapists' personal characteristics and professional competencies, particularly when coded by colleagues within small professional communities. While existing ethical frameworks address research participants generally, they lack specific guidance for the unique vulnerabilities of therapists who are simultaneously research subjects and professional practitioners. We propose targeted considerations for ethical research design, including enhanced informed consent procedures, structural safeguards for managing power differentials, and privacy protections tailored to professional contexts. This theoretical exploration aims to highlight overlooked ethical complexities and guide future research practices when therapists serve as subjects in psychotherapy research.